IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT, SIKAP DAN PERILAKU POSITIF SISWA DI MADRASAH IBTIDAIYAH NEGERI 7 LAMPUNG UTARA KECAMATAN KOTABUMI SELATAN KABUPATEN LAMPUNG UTARA TAHUN PELAJARAN 2023/2024 - Ulfa Kurnia (UNISAN JURNAL, 2024)
Performance The research problem is the implementation of character education at MIN 7 North Lampung. This research focuses on: (1) How is character education implemented regarding wanting to be happy, behavior and positive results for students at MIN 7 North Lampung (2) What are the problems with implementing character education at MIN 7 North Lampung (3) and what are the supporting factors and constitution of the implementation of this character education. This research aims to describe the implementation of character education. This research uses a qualitative approach technique with descriptive methods. implementing character education for each lesson through: creating graduate competency standards (SKL), preparing standards (SK), preparing learning indicators, learning evaluation strategies, implementing all these improvements with supporting and limiting factors. This has a big meaning, it has research implications, namely that every teacher must have professionalism, be a good worker, have fresh functions, and have credible performance. This means that implementing character education is education with aspects of building morals, (ethics-aesthetics), cognition, feelings and psychomotor actions